RL AND RC CIRCUITS-LAPLACE TRANSFORM - NARESH, P. (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
In this paper, I solved the problems occurred in first order ordinary linear differential equations based on RL and RC CircuitsÂ by using Laplace Transform. Keywords: Laplace transforms, RL and RC Circuites, Differential Equations